Helicobacter pylori y su relación con la diabetes mellitus en adultos mayores que residen en el Hogar “Daniel Álvarez Sánchez” de la ciudad de Loja - Ordoñez Piedra, Kelly Valeria (2022)
H. pylori infection is a public health problem, since it is related to certain gastrointestinal conditions and directly to diabetes mellitus, especially present in the elderly, these patients are a high-risk group, due to the changes they undergo the immune system due to age, preventing the body from responding effectively to the presence of this infection. Given the present situation, this research is based on relating the presence of Helicobacter pylori and diabetes mellitus in older adults from the "Daniel Álvarez Sánchez" Home in the city of Loja; therefore, a quantitative, non-experimental, crossrelational design study was carried out, the study was applied to 72 adults over 60 years of age, of both sexes, including 45 diabetic patients and 27 non-diabetic patients outside the Home, who were found to have H. pylori, in serum by indirect enzyme immunoassay anti-IgM H. pylori, which gave us negative quantitative results, later it was verified with the immunochromatographic test in feces, where the negative results were corroborated, therefore it was concluded that in the population studied they do not present an active infection to H. pylori. In addition, since the results of anti-IgM H. pylori were negative and immunochromatographic in negative feces, the Kappa index statistical test could not be applied and for this same reason the presence of H. pylori could not be related to the Chi square statistical test with diabetes mellitus, so it can be deduced that in the present study there was no correlation between H. Pylori and diabetes mellitus